Loss of cholinergic receptor muscarinic 1 impairs cortical mitochondrial structure and function: implications in Alzheimer’s disease - Sabbir, Mohammad Golam; Swanson, Mamiko; Albensi, Benedict C. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Cholinergic Receptor Muscarinic 1 (CHRM1) is a G protein-coupled acetylcholine (ACh) receptor predominantly expressed in the cerebral cortex. In a retrospective postmortem brain tissues-based study, we demonstrated that severely (≥50% decrease) reduced CHRM1 proteins in the temporal cortex of Alzheimer’s patients significantly correlated with poor patient outcomes. The G protein-mediated CHRM1 signal transduction cannot sufficiently explain the mechanistic link between cortical CHRM1 loss and the appearance of hallmark Alzheimer’s pathophysiologies, particularly mitochondrial structural and functional abnormalities. Therefore, the objective of this study was to analyze the molecular, ultrastructural, and functional properties of cortical mitochondria using CHRM1 knockout (Chrm1-/-) and wild-type mice to identify mitochondrial abnormalities. Methods: Isolated and enriched cortical mitochondrial fractions derived from wild-type and Chrm1-/- mice were assessed for respiratory deficits (oxygen consumption) following the addition of different substrates. The supramolecular assembly of mitochondrial oxidative phosphorylation (OXPHOS)-associated protein complexes (complex I-V) and cortical mitochondrial ultrastructure were investigated by blue native polyacrylamide gel electrophoresis and transmission electron microscopy (TEM), respectively. A cocktail of antibodies, specific to Ndufb8, Sdhb, Uqcrc2, Mtco1, and Atp5a proteins representing different subunits of complexes I-V, respectively was used to characterize different OXPHOS-associated protein complexes. Results: Loss of Chrm1 led to a significant reduction in cortical mitochondrial respiration (oxygen consumption) concomitantly associated with reduced oligomerization of ATP synthase (complex V) and supramolecular assembly of complexes I-IV (Respirasome). Overexpression of Chrm1 in transformed cells (lacking native Chrm1) significantly increased complex V oligomerization and respirasome assembly leading to enhanced respiration. TEM analysis revealed that Chrm1 loss led to mitochondrial ultrastructural defects and alteration in the tinctorial properties of cortical neurons causing a significant increase in the abundance of dark cortical neurons (Chrm1-/- 85% versus wild-type 2%). Discussion: Our findings indicate a hitherto unknown effect of Chrm1 deletion in cortical neurons affecting mitochondrial function by altering multiple interdependent factors including ATP synthase oligomerization, respirasome assembly, and mitochondrial ultrastructure. The appearance of dark neurons in Chrm1-/- cortices implies potentially enhanced glutamatergic signaling in pyramidal neurons under Chrm1 loss condition. The findings provide novel mechanistic insights into Chrm1 loss with the appearance of mitochondrial pathophysiological deficits in Alzheimer’s disease.